What harmful practices? The material scope of animal protection legislation: commentary on Birch on 'Precautionary Principle' - Paez, Eze (2017)
Jonathan Birch proposes a criterion for the subjective scope of animal protection legislation. He says nothing about its material scope: which harmful practices it should regulate. I argue, first, that most moral views would agree that the worst forms of animal exploitation should be legally forbidden, even if there will inevitably be disagreement about some cases of animal experimentation. I also argue that, when feasible, there should be legal provisions to help wild animals.